PHILOSOPHY FROM THE SELF TO ACTION: A READING IN THE HISTORY AND CONCEPT OF THE PHILOSOPHY OF ACTION - Benamor Meftah; Grouni Moussa; Allal Ahmed; Djellab Fatiha (International Journal of Innovative Technologies in Social Science, 2025)
This modest research paper addresses one of the important philosophical concepts that has not enjoyed significant and distinctive presence, nor received its fair share of genuine philosophical research and analysis—namely, the Philosophy of Action. This concept is indeed among those that reflect the true value of philosophy, as it connects ideas with practices and distances philosophy from its abstract nature detached from reality. In this paper, we seek to revisit the historicity and the concept of the Philosophy of Action, trace its philosophical evolution, and return to its earliest sources, beginning with Aristotle and extending to the contemporary era, while highlighting how intellectual and philosophical thought has engaged with the value of action and its presence in various philosophical traditions.